2013
DOI: 10.1002/app.40144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanosilver on the photodegradation of poly(lactic acid)

Abstract: The poly(lactic acid), PLA, mixed with nanosilver in solution easily forms nanocomposite in solid state (after solvent evaporation), which was proved by UV-Vis spectroscopy. This work focuses on photodegradation occurring in PLA films doped with nanosilver. The changes in chemical structure of photodegraded PLA has been determined using FTIR spectroscopy. Differential scanning calorimetry of UV-irradiated PLA samples provided information on polymer glass transition and crystallization/melting processes. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…TiO 2 , when irradiated by UV light in the presence of oxygen, generates reactive radicals such as O 2 •, HOO•, and HO•, which initiate the PLA photodegradation, generating other radicals (CH 2 •, CHCH 2 •, among others). These radicals are introduced into the polymer chain and results in their cleavage into volatile compounds such as CO and CO 2 that desorb, while others by‐products with low volatility become attached to the polymer matrix 27,49,50 …”
Section: Resultsmentioning
confidence: 99%
“…TiO 2 , when irradiated by UV light in the presence of oxygen, generates reactive radicals such as O 2 •, HOO•, and HO•, which initiate the PLA photodegradation, generating other radicals (CH 2 •, CHCH 2 •, among others). These radicals are introduced into the polymer chain and results in their cleavage into volatile compounds such as CO and CO 2 that desorb, while others by‐products with low volatility become attached to the polymer matrix 27,49,50 …”
Section: Resultsmentioning
confidence: 99%
“…Mucha and all [22] performed photodegradation process of polylactide filled with nanosilver at 254 nm wavelength. While discussion the mechanism of photodegradation the authors concluded, that the energy at 254 nm radiation capable of breaking the chemical bonds in polylactide.…”
Section: Fourier Transfer Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…During photodegradation, the T g temperature falls at a much slower rate with the increase of the filler content in the composites. The decrease of T g can be explained by the formation of the low-molecular mass products which plasticise PLA and change macromolecular order [34]. It needs to be emphasised that for polylactide and sample containing 1 % of Nanofil2, the glass transition temperature after 4 h of UV irradiation is no longer noticeable, while in the case of samples containing 3 and 5 mass% of nanofiller, T g of PLA can still be observed even after 16 h of UV exposure.…”
Section: Differential Scanning Calorimetry Analysesmentioning
confidence: 99%